Male and female Asians living with HIV: a text-mining analysis comparing their concerns - Chen, Wei-Ti; Barbour, Russell (Frontiers in Psychology, 2023)
Introduction Asians are “a forgotten population” whose HIV prevention and treatment needs have long been ignored. Studies on people living with HIV/AIDS (PLWHA) have primarily reported on physical and psychological conditions among men and gender minorities. Methods We used data-mining to select words and word patterns from pooled in-depth interviews conducted with 33 women and 12 men (n = 45) who were HIV positive and residing in San Francisco, United States, Shanghai, Beijing, or Taipei, China. We analyzed gender-based data (male vs. female) within the participant responses. Results Disclosure of HIV serostatus was discussed by both genders of PLWHA. Participants were concerned whether they should disclose their diagnosis and how to disclose it to their family members. Specifically, for women, family relationships and financial burdens were discussed most often. In terms of men, HIV disclosure was the key concern followed by disclosure of their sexual preference and concerns over what people were saying about them in the community. Conclusion This project compared and contrasted concerns of Asian HIV-positive men and women. As healthcare providers promoting self-management by HIV-positive individuals of both genders, it is important to consider that there may be significant differences between them. Future interventions should consider how gender role influences self-management strategies in PLWHA and how support can be targeted to achieve a better quality of life for PLWHA.